1975
DOI: 10.1088/0022-3727/8/11/006
|View full text |Cite
|
Sign up to set email alerts
|

The internal friction of Nb-1 at.% substitutional alloys

Abstract: The effect of the separate additions of 1 at % of 13 different substitutional solute atoms on the internal friction spectrum of niobium containing oxygen and nitrogen as interstitial solutes has been studied at a frequency of 1 Hz. The substitutional solute atoms interact elastically and chemically with the interstitial solute atoms forming s-i complexes. The effect of the s-i interactions is to reduce the oxygen and nitrogen Snoek peaks (sometimes to zero) and to introduce into the spectrum new subsidiary pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…Figure 2 shows the anelastic relaxation spectra, internal friction and oscillation frequency, as function of temperature for TNZ + WQ + 670 K/3 h sample, where for the temperature range studied were not observed relaxation processes. The absence of relaxation processes can be associated in first instance, with the hcp structure presented by this alloy, since the interstitial sites, octahedral and tetrahedral, have tetragonal symmetry equal to those atoms in the lattice, so simple interstitial atoms do not produce anelastic relaxation 11,16,17 . Moreover in titanium alloys, like Ti-D-Me (Me being a metal such as Zr or Nb), relaxation processes were found only from the individual atoms of oxygen trapped in the vicinity of substitutional atoms by the distortion that these last produce in the lattice.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Figure 2 shows the anelastic relaxation spectra, internal friction and oscillation frequency, as function of temperature for TNZ + WQ + 670 K/3 h sample, where for the temperature range studied were not observed relaxation processes. The absence of relaxation processes can be associated in first instance, with the hcp structure presented by this alloy, since the interstitial sites, octahedral and tetrahedral, have tetragonal symmetry equal to those atoms in the lattice, so simple interstitial atoms do not produce anelastic relaxation 11,16,17 . Moreover in titanium alloys, like Ti-D-Me (Me being a metal such as Zr or Nb), relaxation processes were found only from the individual atoms of oxygen trapped in the vicinity of substitutional atoms by the distortion that these last produce in the lattice.…”
Section: Resultsmentioning
confidence: 92%
“…Ti-13Nb-13Zr alloy is typically an near-β Ti alloy which, when heat treated up the β-transus temperature and water-quenched posses a hexagonal α´-phase martensite microstructure, but followed by an aging treatment that is transformed into a martensite formed by α-phase (hcp structure) with precipitates of β−phase (bcc structure) [5][6][7] . In general it is of great interest to know in a metallic alloy the behavior of alloying elements and the mechanical properties, specifically the elastic modulus in biomaterials, therefore the mechanical spectroscopy becomes an important tool for characterization because it can provide information about the interaction of the matrix with the solutes atoms (substitutional and interstitial) [8][9][10][11] , besides dynamical elastic modulus (elastic modulus as function of temperature) 12 parameter of great importance from the viewpoint of biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…[3] However, the present Ti-Mo alloys show less deviation than Ti-Nb-O alloys, indicating that Mo atoms exert a weaker influence on the Ti-O Snoek relaxation than Nb atoms do, which agrees with the fact that the Mo-O interaction is relatively weak. [7,9] B. Microstructure and Composition of the Oxygen Dissolved Zones Figure 4 shows the surface microstructure of Ti15-MoO after the surface oxidation treatment observed by SEM and EBSD methods. An oxide zone (about 16 lm) exists in the outmost parts of the specimen, as shown in Figure 4(a).…”
Section: Resultsmentioning
confidence: 99%
“…Ti-Mo alloys and Ti-Nb alloys share some common mechanical properties with b Ti alloys, such as high strength, low modulus, suitable ductility, and superior workability for engineering application. Compared with Nb, Mo is a more effective b-phase stabilizing element for Ti alloys, because the equivalent Mo content efficient to suppress the bfi a¢¢ martensitic transformation to a temperature below room temperature is Mo eq (mass pct) = 1.0Mo + 0.28Nb + 2.9Fe + … [6] On the other hand, previous internal friction studies on Nb-Mo-O [7][8][9] and Nb-Ti-O [7] indicate that Mo-O interaction and Nb-O interaction show different influences on the Snoek-type relaxations in b Ti alloys. It was also confirmed that substitutional solutes of Mo show a beneficial effect on the relative index of relaxation strength of O (relaxation strength at unit oxygen concentration) in the Nb-based alloys.…”
Section: Introductionmentioning
confidence: 99%
“…The internal friction curves as a function of temperature would be decomposed into elemental Debye peaks [8] using the method of successive subtraction (in the present work, Peak Fitting Module of Origin was used), and the anelastic relaxation processes could be identified comparing our data with literature [9][10][11][12].…”
Section: Methodsmentioning
confidence: 99%